Effects of itraconazole and rifampicin on the pharmacokinetics and safety of youkenafil, a novel phosphodiesterase type 5 inhibitor, in healthy Chinese subjects - Wang, Keli; Ding, Juefang; Li, Xianjing; Guo, Wenjing; Zhu, Xingyu; Su, Yue; Sun, Luning; Zhou, Huan; Ding, Li (European journal of pharmaceutical sciences, 2022)
•First report of in vivo and in vitro drug interaction studies on youkenafil.•First report of youkenafil pharmacokinetic parameters in healthy Chinese subjects.•Itraconazole and rifampicin have significant clinical effect on youkenafil. Youkenafil is a novel selective phosphodiesterase type 5 inhibitor to treat erectile dysfunction. In order to study the drug-drug interactions of youkenafil, in vitro experiments were conducted with human liver microsomes and recombinant isoenzymes to identify the effect of cytochrome P450 (CYP) enzymes on the metabolism of youkenafil. Then two clinical studies were performed to investigate the effects of itraconazole and rifampicin (potent CYP3A4/5 inhibitor and inducer, respectively) on the pharmacokinetics of youkenafil and its main metabolite, N-desethyl youkenafil (M1). Each study enrolled thirty healthy male subjects. In study 1, subjects were given a single dose of youkenafil (50 mg on Days 1 and 13) and multiple doses of itraconazole (200 mg once daily from Days 6 to 14). In study 2, subjects were given a single dose of youkenafil (100 mg on Days 1 and 20) and multiple doses of rifampicin (600 mg once daily from Days 6 to 20). The results showed that youkenafil was mainly metabolized through CYP3A4/5 in vitro. Itraconazole increased youkenafil AUC and Cmax by about 12- and 6-fold, respectively, and increased M1 AUC and Cmax by 5- and 1.3-fold, respectively. Conversely, rifampicin reduced youkenafil AUC and Cmax both by about 98%. It did not change the AUC of M1 significantly, but increased the Cmax by 30%. All treatments were well tolerated by subjects in both studies. Therefore, co-administration of youkenafil with potent inhibitors or inducers of CYP3A4/5 should be avoided or carefully monitored. Graphical Abstract [Display omitted] .